1990
DOI: 10.1097/00000658-199004000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Pancreatoduodenectomy

Abstract: Twenty-one years ago, Howard published a paper entitled "Forty-one Consecutive Whipple Resections Without an Operative Mortality." That paper stimulated the present analysis of the last 118 consecutive pancreatoduodenectomies (107 Whipple and 11 total resections) performed at the Surgical University Clinic Mannheim from November 1985 to the present day with no deaths. Ninety-one resections were performed for neoplasms and 27 were for complicated chronic pancreatitis. The preoperative evaluation, operative tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
195
1
13

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,026 publications
(218 citation statements)
references
References 22 publications
9
195
1
13
Order By: Relevance
“…Although there is some evidence that early diagnosis and resection can result in improved long-term survival (51), there is a paucity of specific molecular markers to detect pancreatic adenocarcinoma or to identify patients at higher risk for cancer development (39,40). Further study of the differential expression of CCK receptors may reveal CCK-A receptors as a useful biomarker for pancreatic adenocarcinoma diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some evidence that early diagnosis and resection can result in improved long-term survival (51), there is a paucity of specific molecular markers to detect pancreatic adenocarcinoma or to identify patients at higher risk for cancer development (39,40). Further study of the differential expression of CCK receptors may reveal CCK-A receptors as a useful biomarker for pancreatic adenocarcinoma diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…In recent series, resection for cure has been possible in 15 to 20% of unselected patients21 and in 29 to 34% of patients screened as suitable candidates for curative resection.7.S Representative recent studies have reported 5 year survival rates for pancreatic cancer of 6.8%, 9%, 17%, and 25%. [9][10][11][12] In tumors other than ductal adenocarcinoma, 5 year survival is higher-for example, 9% versus 36% in Wade and coworkers' study.to Mortality after Whipple pancreaticoduodenectomy resection has decreased. Several decades ago mortality ranged from 15 to 25%.1 More recently, mortality rates varying from 012.13 to 8%1.10 have been reported.…”
mentioning
confidence: 99%
“…[28][29][30] We analyzed the correlations between clinicopathological indices and immunohistochemical staining for surgical specimens curatively resected from primary pancreatic adenocarcinoma using several monoclonal antibodies: anti-CD44s, anti-CD44v6 (exon 11) antibody and a recently developed anti-CD44v2 (exon 7) antibody whose specificity for the CD44v2 epitope has been confirmed by Borgya et al 31) …”
mentioning
confidence: 99%